Exploring the “Myth of Parity” in State Taxation: State Court Decisions Interpreting Public Law 86—272 - Bradley W. Joondeph (Washington University Journal of Law & Policy, 2003)
Although several scholars have explored the question of parity between federal and state courts in a variety of other contexts, the empirical question whether state courts are systematically biased against taxpayers seeking the protection of federal law has gone largely unexamined. This Essay offers a preliminary exploration of that issue. Specifically, it presents a study of all reported state court decisions interpreting Public Law 86–272, a federal statute enacted in 1959 that provides businesses with immunity from state income taxes when they keep their activities in the taxing state beneath a specific threshold. State court decisions interpreting Public Law 86–272 may provide a means for measuring systemic bias.
Keywords: Income tax -- United States -- States; Intergovernmental tax relations; Law -- Interpretation & construction -- United States -- States; Federal jurisdiction